Corporate Communication as One of the Basic Attributes of Corporate Identity – Case Study of Chocolate Milka - Ľudmila Nagyová,; Ingrida Košičiarová,; Martina Sedliaková, (Communication Today, 2025)
One of the basic aims of all companies doing business in the present market environment is to distinguish themselves from their competition. The basic way how to do it is to create a unique corporate identity, i.e. a functioning mixture of corporate culture, design, product and corporate communication. The research article deals with the issue of corporate communication as one of the basic attributes of corporate identity. The text’s objective is to bring new information about corporate comunication of Milka chocolate, as well as to determine Slovak respondents’ opinions on the level of external communication of Milka and the possible ways of improving it. The research methodology included a questionnaire survey conducted in the electronic form, which was shared through social media (the research sample involved 1,518 respondents from all regions of the Slovak Republic) and testing of a smaller number of respondents via the emWave PC system (the tested group consisted of 20 participants who were randomly selected from the previous research sample). As we were interested in conducting a deeper analysis of the obtained results, four assumptions and eight hypotheses were formulated and then tested using Pearson’s chi-square test, Cramer’s contingency coefficient and Phi coefficient. As the results of the research show, the Slovak respondents perceive Milka’s corporate communication quite positively – almost 76% of the surveyed respondents claim that they consider it to be interesting and unobtrusive; more than 49% and almost 40% of the respondents say that they think Milka’s promotion is adequate and good enough, respectively; more than 60% of them see Milka’s advertisements as attractive and almost 55% of the participants think that Milka-related advertising is able to motivate the potential buyers to purchase these products.